Gang activity in San Bernardino, California: A needs assessment for Operation Phoenix - Rogers, Mario Leone (2008)
This research study examined an innovative gang approach in the city of San Bernardino called Operation Phoenix. The purpose of this study was to conduct a needs assessment for Operation Phoenix. This qualitative and quantitative study examined how effective Operation Phoenix was in the prevention, intervention, and suppression of gang activity in the city of San Bernardino. In addition it assessed the unique needs of this comprehensive gang program